Meaning Used By Pranatacara in Javanese Wedding Ceremony “Panggih Manten” - Muhammad Natsir; Tiara Artha Dewi; Bahagia Saragih (Britain International for Academic Research (BIAR-Publisher), 2022)
This study used the descriptive qualitative method. The qualitative method was a research procedure which results in descriptive data, including written and oral word from the research objectives. The data used in this study were taken from the speech utterances by Pranatacara in